PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM PUBLIK PADA PERUSAHAAN PERBANKAN YANG DI TAKE OVER OLEH LEMBAGA PENJAMIN SIMPANAN (TINJAUAN KASUS PT. BANK CENTURY, TBK) - , RAHMAT SETIABUDI SOKONAGORO; , Prof. Dr. Nindyo Pramono, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to determine the application of legal protection for public shareholders in the takeover process of PT. Century Bank, Tbk by the Indonesian Deposit Insurance Corporation, and also about the efforts and constraints faced by the Capital Market Supervisory Agency and Financial Institution (BapepamâLK) as the capital market authorities and the Indonesian Stock Exchange as the organizer of the capital market. Research on the Legal Protection of the Public Shareholders of the Banking Companies Takeover by the Indonesian Deposit Insurance Corporation (Case Review of PT. Bank Century, Tbk) is juridical normative research or in other hand, based on library research in order to obtain secondary data in the legal field. In order to complete data from literature, the field research was conducted. The research took place in Jakarta, at Indonesia Deposit Insurance Corporation, Capital Market Supervisory Agency and Financial Institutions and Capital Market Reference Center. The result shows that the takeover process of PT. Century Bank, Tbk by the Indonesian Deposit Insurance Agency was made during the state affected the condition of the global financial crisis. The aim is to rescue takeover of the banking and financial system in Indonesia. However, the takeover ignores the rights of public shareholders. The acquisition was done with the legal basis of Law Number 40 Year 2007 regarding Limited Liability Company and is specifically based on Law Number 24 Year 2004 concerning the Deposit Insurance Agency and its implementing regulations. Public company takeover regulation and takeover rules for the limited companies ignored by Indonesia Deposit Insurance Corporation. The results also indicated that the Capital Market Supervisory Agency or less a role in protecting the Public Shareholders of Century Bank. However, measures to protect public shareholders have been carried out by the Indonesia Stock Exchange as the steering.